1972
DOI: 10.1177/00220345720510031901
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Mg, Na, Cl, Al, and Ca in Human Dental Calculus by Neutron Activation Analysis and High Resolution Gamma-Spectrometry

Abstract: The concentrations of magnesium, sodium, chlorine, aluminum, and calcium in pooled human dental calculus dried to constant weight at 105 C were determined by instrumental neutron activation analysis. Their mean concentrations were 0.50 ± 0.04%, 0.37 ± 0.03%, 0.09 ± 0.01%, 96.08 ± 14.63 ppm, and 28.04 ± 1.70%, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1973
1973
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…As shown in previous studies Ca, O, P, and C constitute the main elements in enamel (Nelson et al, 2002; Lou et al, 2008). Analyses of enamel using neutron activation and with X-ray energy dispersive spectroscopy show values comparable with those found in this study (Retief et al, 1970, 1971; Gotierrez-Salazar & Reyes-Gasga, 2003). Measured values of different elements may vary considerably, not only between different teeth but also between different morphological locations within the tooth, where especially the enamel closest to the surface is heterogeneous (Weatherell et al, 1974; Sabel et al, 2009 a ).…”
Section: Discussionsupporting
confidence: 90%
“…As shown in previous studies Ca, O, P, and C constitute the main elements in enamel (Nelson et al, 2002; Lou et al, 2008). Analyses of enamel using neutron activation and with X-ray energy dispersive spectroscopy show values comparable with those found in this study (Retief et al, 1970, 1971; Gotierrez-Salazar & Reyes-Gasga, 2003). Measured values of different elements may vary considerably, not only between different teeth but also between different morphological locations within the tooth, where especially the enamel closest to the surface is heterogeneous (Weatherell et al, 1974; Sabel et al, 2009 a ).…”
Section: Discussionsupporting
confidence: 90%
“…Quantitative studies of the elemental composition of dental enamel are scarce and commonly the measurements are regarded as semi-quantitative or presented as ratios to the Ca content (Retief et al, 1970, 1971; Shaw & Yen, 1972). Analyses of human enamel using our method and by neutron activation and EDS (Retief et al, 1970, 1971; De Menezes Oliveira et al, 2010) shown in Table 2 show values comparable with the bovine enamel results of this study. Other studies of human enamel by X-ray EDS show large deviations from our results and do not describe their methods or discuss their accuracy in any detail (Gotierrez-Salazar & Reyes-Gasga, 2003; Mahoney et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that Al is a normal constituent of first and adult teeth (457, 458) which fluctuates in the various anatomical portions of the tooth with age (459, 460). Discolored areas of sound teeth have been observed to contain markedly elevated concentrations of both Al and F. Human dental calculus has also been shown to contain high concentrations of Al (461) which have been shown to inhibit alkaline phosphatase (462) and alkaline phosphomonoesterase (463) from human dental plaque. Studies of caries-free, carious, and impacted human teeth have demonstrated that the caries-free teeth Environmental Health Perspectives contain more or less Al than diseased teeth, depending upon the anatomical part studied and the stage of the disease (464)(465)(466).…”
Section: August 1974mentioning
confidence: 99%